IMPROVING PERFORMANCE IN AN ALUMINUM EXTRUSION PLANT USING DISCRETE EVENT SIMULATION: A CASE STUDY - Al-Hawari, Tarek; Naimi, Ahmad; Zurikat, Hashim; Obeid, Mohamad Abu (MATTER: International Journal of Science and Technology, 2019)
Simulation has been used in many industrial applications for performance improvement. It excels over other system analysis methods in its high flexibility and ability to model system details with high accuracy. In this study, Discrete Event Simulation (DES) is used to improve the performance of an aluminum extrusion plant. A case study is presented in a local factory in which problems are identified, and their effects on efficiency are monitored. The main problem noticed was high production rates with respect to demand rates which resulted in large amounts of work-in-process (WIP) inventory. It was found that the current base system is unstable and suggestions were made to lower production rates in order to stabilize it. Average WIP was reduced by 324% once the system was stabilized with only 1.77% difference in weekly throughput which improved the system considerably. Next, alternatives were suggested to improve throughput and reduce WIP while maintaining stability. The alternative with optimized batch sizes had the best improvement in throughput of 3.54%. The combined model with optimized batch sizes and an added pool for chemical treatment had the most WIP versus other alternatives.